Finding Magnetopause Standoff Distance Using a Soft X‐ray Imager: 2. Methods to Analyze 2‐D X‐ray Images. Issue 12 (23rd December 2022) - Samsonov, Andrey; Sembay, Steven; Read, Andrew; Carter, Jennifer Alyson; Branduardi‐Raymont, Graziella; Sibeck, David; Escoubet, Philippe
Abstract: The Earth's magnetosheath and cusps are the sources of soft X‐rays. In the accompanying paper (Part 1) and this paper, we discuss the methods of finding the magnetopause position by analyzing the X‐ray images. We use the software developed for the Soft X‐ray Imager (SXI) on board the forthcoming Solar wind Magnetosphere Ionosphere Link Explorer (SMILE) mission. We show how to find the maximum SXI count rate in noisy count maps. We verify the assumption that the maximum of the X‐ray emissivity integrated along the Line‐of‐Sight ( Ix ) is tangent to the magnetopause. We consider two cases using two MHD models and apply different methods of magnetospheric masking. Overall, the magnetopause is located close to the maximum Ix gradient or between the maximum Ix gradient and the maximum Ix depending on the method used. But since the angular distance between the maximum Ix gradient and the maximum Ix is relatively small (about 3°), the maximum Ix might be used as an indicator of the outer boundary of a wide magnetopause layer usually obtained in MHD simulations. Plain Language Summary: This is the second of two papers presenting the techniques to estimate the Earth's magnetopause location (the outer boundary of the magnetosphere) under the impact of the highly dynamic solar wind. Our knowledge of the overall shape of the magnetopause will be vastly improved when we start using X‐ray imagers to monitor large areas around this boundary as the solar wind varies. In this second paper of the series, we make use of the X‐ray emissions in the vicinity of the Earth simulated in the first paper for two case studies with vastly different incoming solar wind conditions. Here we examine different methods of how to extract the magnetopause shape and position from X‐ray maps of the type that will be returned by the X‐ray imager due to flying on the SMILE mission. Key Points: Different methods of finding the location and shape of the magnetopause from X‐ray images give consistent results Maximum integrated emissivity indicates the outer boundary of the magnetopause This work is made in preparation for the forthcoming Solar wind Magnetosphere Ionosphere Link Explorer mission